The monist - Hegeler, Edward C., 1835-1910.; Hegeler Institute (Chicago : Open Court Pub. Co., 1890)
Vols. 2 and 5 include appendices.
"An international quarterly journal of general philosophical inquiry."
Founded by Edward C. Hegeler.
Suspended between July 1936 and fall 1962.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Vols. 1-17, 1890-1907. 1 v.; Vols. 47-69, 1962-86. 1 v.
digitized
Keywords: Philosophy -- Periodicals; Philosophie -- Périodiques.; Philosophy; Filosofie; Electronic journals